Komparasi Kualitas Fisikokimia Simplisia Bunga Telang Dengan Beberapa Perbedaan Perlakuan Pasca Panen - Dimas Aji Pratama; Endah Puspitojati; Siwitri Munambar (Politeknik Negeri Lampung., 2025)
This study aimed to determine the quality of dried butterfly pea flowers obtained by several post-harvest handling treatments. Post-harvest treatment of butterfly pea flowers according to SOPs includes harvesting, wet sorting, washing and draining, weighing, drying, dry sorting, and packaging. This study consisted of four post-harvest treatments, including P1 (without washing and sorting, direct sun drying), P2 (without washing and sorting, drying using food dehydrator), P3 (with washing and sorting, indirect sun drying), and P4 (with washing and sorting, drying food dehydrator). All treatments were analysed for dried flower quality, including water content, antioxidant content, and organoleptic quality. The results showed that there was a significant difference in the moisture content of butterfly pea flowers with four post-harvest treatments. P3 and P4 obtained lower moisture content than P1 and P2, which were 9.7% and 10.7%, respectively. Washing, wet sorting, and dry sorting are part of post-harvest handling following SOPs. The antioxidant content data showed no significant difference from the four treatments, but the highest free radical inhibition was obtained from the P3 treatment, which was 80%. From this study, it can be concluded that good post-harvest treatment of butterfly pea flowers consisted of harvesting activities, wet sorting, washing and draining, weighing, undirect sunlight drying or food dehydrator drying, dry sorting, and packaging.